Remote Hemorrhage in the Cerebellum and Temporal Lobe after Lumbar Spine Surgery. (3rd August 2015) - Watanabe, Shotaro; Ohtori, Seiji; Orita, Sumihisa; Yamauchi, Kazuyo; Eguchi, Yawara; Aoki, Yasuchika; Nakamura, Junichi; Miyagi, Masayuki; Suzuki, Miyako; Kubota, Gou; Inage, Kazuhide; Sainoh, Takeshi; et al.
Abstract : Cerebellar hemorrhage remote from the site of surgery can complicate neurosurgical procedures. However, this complication after lumbar surgery is rare. Furthermore, hemorrhage in both the cerebellum and the temporal lobe after spine surgery is rarer still. Herein we present a case of remote hemorrhage in both the cerebellum and the temporal lobe after lumbar spine surgery. A 79-year-old woman with a Schwannoma at the L4 level presented with low back and bilateral leg pain refractory to conservative management. Surgery was undertaken to remove the Schwannoma and to perform posterior fusion. During the surgery, the dura mater was removed in order to excise the Schwannoma. Reconstruction of the dura mater was performed; postoperatively the patient had a cerebrospinal fluid leak. Five days after surgery, clouding of consciousness started gradually, and hemorrhage in the cerebellum and the temporal lobe was revealed by computed tomography. Emergent evacuation of the hemorrhage was performed and the patient recovered consciousness after the surgery. Leakage of cerebrospinal fluid may have induced this hemorrhage. While rare, intracranial hemorrhage after spine surgery can occur, sometimes requiring emergent intervention.